Positive electrode material precursor and preparation method thereof, positive electrode material for sodium ion battery and preparation method thereof, sodium ion battery

By adjusting the feed position and process parameters of the metal salt solution, the high spherical shape and narrow particle size distribution of the precursor of the positive electrode material of the sodium ion battery are solved, the Cu element segregation problem is significantly improved, and the capacity and circulation performance of the sodium ion battery are simplified. The process flow is completed.

CN116081707BActive Publication Date: 2025-01-10BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211657909.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-01-10
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The precursor of the positive electrode material in sodium ion batteries has low spherical shape, wide particle size distribution, and easy segregation of the metal Cu element, resulting in low capacity and poor circulation performance.

Method used

By adjusting the feed position and process parameters of the metal salt solution, controlling the proportion of ammonia and Cu ions, a two-stage synthesis reaction is adopted to achieve uniform co-precipitation of Cu elements and other metal elements, and a high spherical and narrow particle size distribution is prepared. precursor of the cathode material.

Benefits of technology

It significantly improves the capacity and circulation performance of sodium ion batteries, ensures the uniform distribution of Cu elements, overcomes the problem of Cu element segregation, and has a simple process, low energy consumption, and is easy to use in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116081707B_ABST
    Figure CN116081707B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion batteries, and discloses a positive electrode material precursor, a positive electrode material for a sodium ion battery, a preparation method thereof, and a sodium ion battery. The positive electrode material precursor is spherical and / or quasi-spherical; the sphericity Q of the positive electrode material precursor satisfies: 90%<Q<100%; the D 10 , D 50 and D 90 Satisfy: 0.55<K 90 =(D 90 ‑D 10 ) / D 50 <0.85;wherein, Q=4π×S / (L 2 )×100%, S is the projected area of ​​the precursor secondary particles, and L is the perimeter of the projection of the precursor secondary particles. The positive electrode material precursor has high sphericity and narrow particle size distribution, and in particular, has uniform metal element distribution. When the positive electrode material prepared from the positive electrode material precursor is used in a sodium ion battery, the capacity performance and cycle performance of the sodium ion battery can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion battery materials, and in particular to a positive electrode material precursor and a preparation method thereof, a positive electrode material for a sodium ion battery and a preparation method thereof, and a sodium ion battery. Background Art

[0002] In today's society, electricity is closely related to our work and life. Once the power is cut off, many serious consequences will occur. In order to solve the contradictory relationship between electricity waste and insufficient electricity, large-scale energy storage has been developed. Among the many energy storage methods, secondary battery energy storage is the most convenient system to use and maintain. In secondary battery energy storage, lithium-ion batteries are the most mature, but due to the limited reserves of lithium resources, it is estimated that at the current mining rate, the lithium resources can be mined for no more than 50 years. Compared with lithium-ion batteries, the sodium resources used in sodium-ion batteries are abundant, low-priced and environmentally friendly, so the vigorous development of sodium-ion batteries will help promote the development of large-scale energy storage.

[0003] Cu has the advantages of wide availability, low price and high capacity, and has attracted much attention recently. However, the precipitation coefficients KSP of Mn(OH)2, Ni(OH)2, Fe(OH)2 and Cu(OH)2 are 1.9×10 -15 , 2×10 -15 , 8×10 -16 and 22×10 -20 It can be seen that when the precursor material is prepared by the co-precipitation method, the Cu element is very easy to segregate. The segregation of the Cu element in the precursor material will be transferred to the positive electrode material, which will bring great problems to the sodium ion battery, such as low capacity and poor cycle performance. Therefore, how to uniformly introduce the Cu element into the sodium ion battery precursor by the co-precipitation method is a great challenge. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low sphericity, wide particle size distribution and easy segregation of metal elements, especially Cu element, in the prior art of the positive electrode material precursor for sodium ion batteries, and to provide a positive electrode material precursor and a preparation method thereof, a positive electrode material for sodium ion batteries and a preparation method thereof, and a sodium ion battery. The positive electrode material precursor has high sphericity and narrow particle size distribution, in particular, has a uniform distribution of metal elements, and when the positive electrode material prepared from the positive electrode material precursor is used in a sodium ion battery, the capacity performance and cycle performance of the sodium ion battery can be significantly improved.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positive electrode material precursor, characterized in that the positive electrode material precursor is spherical and / or quasi-spherical; the sphericity Q of the positive electrode material precursor satisfies: 90%<Q<100%;

[0006] The cathode material precursor D 10 , D 50 and D 90 Satisfy: 0.55<K 90 =(D 90 -D 10 ) / D 50 <0.85;

[0007] Where, Q = 4π × S / (L 2 )×100%, S is the projected area of ​​the precursor secondary particles, and L is the projected circumference of the precursor secondary particles.

[0008] A second aspect of the present invention provides a method for preparing a positive electrode material precursor, characterized in that the preparation method comprises the following steps:

[0009] (1) mixing a soluble manganese salt, a ferrous salt, a nickel salt and an optional M salt with water to obtain a first metal salt solution; mixing a soluble copper salt with water to obtain a second metal salt solution; mixing a precipitant with water to obtain a precipitant solution;

[0010] (2) introducing the first metal salt solution into the reactor through a first liquid inlet pipe, and introducing the second metal salt solution into the reactor through a second liquid inlet pipe; the distance L1 between the first liquid inlet pipe and the bottom of the reactor and the distance L2 between the second liquid inlet pipe and the bottom of the reactor satisfy: γ = L2 / L1>1;

[0011] (3) Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the precipitant solution and ammonia water are simultaneously introduced into a reaction vessel to perform a synthesis reaction to obtain a slurry, which is then aged, washed and filtered to obtain a filter cake, which is then dried to obtain the positive electrode material precursor, wherein the ratio β of the amount of ammonia water to the amount of copper ions is controlled to satisfy: 0<β≤0.9.

[0012] The third aspect of the present invention provides a positive electrode material precursor prepared by the above preparation method.

[0013] A fourth aspect of the present invention provides a positive electrode material for a sodium ion battery, characterized in that the positive electrode material for a sodium ion battery is prepared from the above-mentioned positive electrode material precursor.

[0014] A fifth aspect of the present invention provides a method for preparing the above-mentioned positive electrode material for a sodium ion battery, characterized in that the method comprises the following steps:

[0015] The positive electrode material precursor is mixed with a sodium source and then sintered to obtain the positive electrode material.

[0016] A sixth aspect of the present invention provides a sodium ion battery, characterized in that the sodium ion battery comprises the above-mentioned positive electrode material for sodium ion battery.

[0017] Through the above technical scheme, the positive electrode material precursor and the preparation method thereof, the positive electrode material for sodium ion battery and the preparation method thereof, and the sodium ion battery provided by the present invention achieve the following beneficial effects:

[0018] The positive electrode material precursor provided by the present invention has high sphericity and narrow particle size distribution, in particular, has uniform metal element distribution, and when the positive electrode material prepared from the positive electrode material precursor is used in a sodium ion battery, the capacity performance and cycle performance of the sodium ion battery can be significantly improved. Specifically, the positive electrode material prepared from the positive electrode material precursor also has high sphericity, narrow particle size distribution and uniform metal element distribution, so that the prepared sodium ion battery has excellent capacity performance and cycle performance.

[0019] In the preparation method of the positive electrode material precursor for sodium ions provided by the present invention, the preparation process parameters are controlled by changing the feeding position of the metal salt solution at the same time, especially by controlling the ratio of the amount of the complexing agent ammonia water to the Cu ion substance, so that the Cu element and other metal elements can be uniformly co-precipitated, so that the prepared positive electrode material precursor has high sphericity and narrow particle size distribution, especially, has a uniform distribution of metal elements, and overcomes the problem of Cu element segregation. In addition, the method and equipment are similar to those used in the lithium battery industry, can be directly switched and transformed, the process is simple and the energy consumption is low, and it is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the reactor of the present invention.

[0021] Figure 2 This is a SEM image of the positive electrode material precursor P1 provided in Example 1 at 30K times.

[0022] Figure 3 This is a SEM image of the positive electrode material precursor P1 provided in Example 1 at 2K times.

[0023] Figure 4 This is a SEM image of the positive electrode material precursor DP1 provided in Comparative Example 1 at 30K times.

[0024] Figure 5 This is a SEM image of the positive electrode material precursor DP1 provided in Comparative Example 1 at 2K times.

[0025] Figure 6 The distribution diagram of Mn, Ni, Fe and Cu elements obtained by performing EDS energy spectrum scanning on the positive electrode material precursor P1 of Example 1.

[0026] Figure 7 Schematic diagram of the actual content of Cu element in the positive electrode material precursor P1 of Example 1.

[0027] Figure 8 This is the distribution diagram of Mn, Ni, Fe and Cu elements obtained by performing EDS energy spectrum scanning on the positive electrode material precursor DP1 of comparative example 1.

[0028] Fig. 9 This is a schematic diagram of the measured value of the Cu element content in the positive electrode material precursor DP1 of comparative example 1.

[0029] Fig.10 Schematic diagram of the actual content of Cu element in the positive electrode material A1 of Application Example 1.

[0030] Fig.11 Schematic diagram of the actual content of Cu element in the positive electrode material D1 of comparative application example 1.

[0031] Description of Reference Numerals

[0032] 1-reactor; 2-stirring paddle; 3-ammonia solution inlet pipe; 4-precipitant solution inlet pipe; 5-first inlet pipe; 6-second inlet pipe. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] The first aspect of the present invention provides a cathode material precursor, characterized in that the cathode material precursor is spherical and / or quasi-spherical; the sphericity Q of the cathode material precursor satisfies: 90%<Q<100%;

[0035] The cathode material precursor D 10 , D 50 and D 90 Satisfy: 0.55<K 90 =(D 90 -D 10 ) / D 50 <0.85;

[0036] Where, Q = 4π × S / (L 2 )×100%, S is the projected area of ​​the precursor secondary particles, and L is the projected circumference of the precursor secondary particles.

[0037] In the present invention, the high sphericity and narrow particle size distribution of the positive electrode material precursor can significantly improve the capacity performance and cycle performance of the sodium ion battery when the positive electrode material prepared from the positive electrode material precursor is used in a sodium ion battery.

[0038] In the present invention, D 90 It refers to the particle size when the volume cumulative value in the particle size distribution is 90%; D 50 It refers to the particle size when the volume cumulative value in the particle size distribution is 50%; D 10 It refers to the particle size when the volume cumulative value in the particle size distribution is 10%.

[0039] In the present invention, the cathode material precursor D 10 , D 50 and D 90 Measured by laser particle size analyzer.

[0040] In the present invention, the area S of the positive electrode material precursor particle is the projected area of ​​the secondary particle in the SEM electron microscope image; the perimeter L of the positive electrode material precursor particle is the projected perimeter of the secondary particle in the SEM electron microscope image.

[0041] Furthermore, 93%<Q<100%.

[0042] Furthermore, 0.57<K 90 =(D 90 -D 10 ) / D 50 <0.75.

[0043] According to the present invention, the cathode material precursor is a secondary particle formed by agglomeration of primary particles.

[0044] According to the present invention, the cathode material precursor has a composition shown in Formula I:

[0045] Mn x Fe y Ni z Cu w M a (OH)2 Formula I;

[0046] Among them, 0.3≤x≤0.5, 0.2≤y≤0.4, 0.1≤z≤0.3, 0.05≤w≤0.15, a=1-xyzw; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.

[0047] Further, 0.35<x<0.45, 0.25<y<0.35, 0.15<z<0.25, 0.08<w<0.12, a=1-xyzw.

[0048] Furthermore, M is selected from at least one of Al, Ti, Nb, V, Mg, B and Y, and preferably M is Mg.

[0049] According to the present invention, the actual content of Cu element at any position in the positive electrode material precursor is w' and the theoretical content of Cu element in the positive electrode material precursor is w, which satisfies the following relationship:

[0050] Δw p =︱w'-w︱ / w<10%.

[0051] In the present invention, the metal elements in the positive electrode material precursor are evenly distributed, and in particular, the actual content of the Cu element at any position is slightly different from the theoretical content, indicating that the Cu element in the positive electrode material precursor is evenly distributed without segregation. Therefore, when the positive electrode material prepared from the positive electrode material precursor is used in a sodium ion battery, the capacity performance and cycle performance of the sodium ion battery can be significantly improved.

[0052] In the present invention, the actual content of Cu element at any position in the positive electrode material precursor is w' measured by EDS method.

[0053] In the present invention, when the actual content w' of the Cu element is tested, the area of ​​the selected position accounts for 1-30% of the area of ​​the selected positive electrode material precursor particles. In the present invention, when ensuring that the area of ​​the selected position meets the above range when testing the actual content w' of the Cu element, the feasibility of the test can be guaranteed, and the averaging effect can be effectively avoided, so that the uniformity of the distribution of the Cu element can be better characterized.

[0054] Furthermore, Δw p =︱w'-w︱ / w<5%.

[0055] According to the present invention, the median particle size D of the positive electrode material precursor is 50 It is 3-10 μm, preferably 3.5-8 μm, and more preferably 3.5-5.5 μm.

[0056] According to the present invention, the bulk density AD of the cathode material precursor is 0.3-1 g / cm 3 , preferably 0.45-0.75g / cm 3 .

[0057] According to the present invention, the tap density TD of the positive electrode material precursor is 0.6-1.5 g / cm 3 , preferably 0.7-1.3 g / cm3 .

[0058] According to the present invention, the specific surface area BET of the cathode material precursor is 20-70 m 2 / g, preferably 30-45m 2 / g.

[0059] A second aspect of the present invention provides a method for preparing a positive electrode material precursor, characterized in that the preparation method comprises the following steps:

[0060] (1) mixing a soluble manganese salt, a ferrous salt, a nickel salt and an optional M salt with water to obtain a first metal salt solution; mixing a soluble copper salt with water to obtain a second metal salt solution; mixing a precipitant with water to obtain a precipitant solution;

[0061] (2) introducing the first metal salt solution into the reactor through a first liquid inlet pipe, and introducing the second metal salt solution into the reactor through a second liquid inlet pipe; the distance L1 between the first liquid inlet pipe and the bottom of the reactor and the distance L2 between the second liquid inlet pipe and the bottom of the reactor satisfy: γ = L2 / L1>1;

[0062] (3) Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the precipitant solution and ammonia water are simultaneously introduced into a reaction vessel to perform a synthesis reaction to obtain a slurry, which is then aged, washed and filtered to obtain a filter cake, which is then dried to obtain the positive electrode material precursor, wherein the ratio β of the amount of ammonia water to the amount of copper ions is controlled to satisfy: 0<β≤0.9.

[0063] In the present invention, in the preparation method of the positive electrode material precursor, the preparation process parameters are controlled by changing the feeding position of the metal salt solution, in particular, the ratio of the amount of the complexing agent ammonia water to the Cu ion substance is controlled, so that the Cu element and other metal elements can be uniformly co-precipitated, so that the prepared positive electrode material precursor has high sphericity and narrow particle size distribution, in particular, has a uniform distribution of metal elements, and overcomes the problem of Cu element segregation. In addition, the method and equipment are similar to those used in the lithium battery industry, can be directly switched and transformed, the process is simple and the energy consumption is low, and it is easy to realize industrialization.

[0064] Furthermore, 2≤γ≤8.

[0065] Furthermore, 0.15≤β≤0.6, and further, 0.15≤β≤0.4.

[0066] In the present invention, the soluble manganese salt is selected from at least one of manganese sulfate, manganese chloride and manganese nitrate.

[0067] In the present invention, the ferrous salt is selected from at least one of ferrous sulfate, ferrous chloride and ferrous nitrate.

[0068] In the present invention, the nickel salt is selected from at least one of nickel sulfate, nickel chloride and nickel nitrate.

[0069] In the present invention, the soluble copper salt is selected from at least one of copper sulfate, copper chloride and copper nitrate.

[0070] In the present invention, the M salt is a salt containing the M element.

[0071] In the present invention, the precipitant is selected from at least one of NaOH, KOH and LiOH.

[0072] According to the present invention, the conditions of the synthesis reaction include: a reaction temperature of 40-70° C. and a stirring speed of 500-1000 rpm.

[0073] In a specific embodiment of the present invention, the synthesis reaction comprises the following steps:

[0074] S1, controlling the pH of the reactor to 11.5-12.5, and carrying out the first stage synthesis reaction;

[0075] S2. Control the pH of the reactor to 10.5-11.5 and carry out the second stage synthesis reaction.

[0076] In the present invention, the first stage of the synthesis reaction is the granulation stage, and the second stage of the synthesis reaction is the growth stage.

[0077] In the present invention, the synthesis reaction is carried out in the above two-stage manner, which is conducive to making the prepared precursor material have a narrow particle size distribution and high sphericity.

[0078] According to the present invention, the reaction temperature of the first stage synthesis reaction is 40-70° C., the reaction time is 5-30 h, and the stirring speed is 500-1000 rpm.

[0079] Furthermore, the reaction temperature of the first stage synthesis reaction is 45-65° C., the reaction time is 10-25 h, and the stirring speed is 600-800 rpm.

[0080] According to the present invention, the temperature of the second stage synthesis reaction is 40-70° C., the reaction time is 40-120 h, and the stirring speed is 500-1000 rpm.

[0081] Furthermore, the reaction temperature of the second stage synthesis reaction is 45-65° C., the reaction time is 50-80 h, and the stirring speed is 550-850 rpm.

[0082] In the present invention, when the reaction time of the synthesis reaction is 5-30 hours, preferably 10-25 hours, the pH value in the reactor is adjusted, and the synthesis reaction transitions from the first stage synthesis reaction to the second stage synthesis reaction.

[0083] According to the present invention, the synthesis reaction makes the solid content of the slurry in the reactor be 200-1000 g / L.

[0084] Furthermore, the synthesis reaction makes the solid content of the slurry in the reactor be 400-800 g / L.

[0085] In a specific embodiment of the present invention, when the particle size of the cathode material precursor in the reactor grows to a target size, the liquid feeding is stopped, and the slurry is aged, washed, and filtered.

[0086] In the present invention, conventional aging conditions in the art are used for aging.

[0087] According to the present invention, the washing conditions include: washing by alternating alkali washing and water washing until the filtrate is neutral.

[0088] According to the present invention, the drying conditions are: drying temperature is 100-150° C., and drying time is 3-24 hours.

[0089] In a specific embodiment of the present invention, Figure 1 As shown, the positive electrode material precursor is prepared according to the following steps:

[0090] S1, mixing a soluble manganese salt, a ferrous salt, a nickel salt and optionally an M salt with water to obtain a first metal salt solution; mixing a soluble copper salt with water to obtain a second metal salt solution; mixing a precipitant with water to obtain a precipitant solution;

[0091] S2. The first metal salt solution is introduced into the reactor 1 through the first liquid inlet pipe 5, and the second metal salt solution is introduced into the reactor 1 through the second liquid inlet pipe 6; the distance L1 between the first liquid inlet pipe and the bottom of the reactor and the distance L2 between the second liquid inlet pipe and the bottom of the reactor satisfy: γ=L2 / L1>1.

[0092] S3. Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the precipitant solution and the ammonia water are respectively fed into the reactor 1 through the first liquid inlet pipe 5, the second liquid inlet pipe 6, the precipitant solution liquid inlet pipe 4 and the ammonia water liquid inlet pipe 3 in parallel to carry out a synthesis reaction to obtain a slurry, which is then aged, washed and filtered to obtain a filter cake, which is dried to obtain the positive electrode material precursor, wherein the ratio β of the amount of ammonia water to the amount of copper ion is controlled to satisfy: 0<β≤0.9.

[0093] Specifically, the synthesis reaction is divided into two stages. Among them, the first stage synthesis reaction is the granulation stage, the pH of the reactor is controlled to be 11.5-12.5, the reaction temperature is 40-70°C, the stirring speed of the stirring paddle 2 is 500-1000rpm, and the total reaction is 5-30h. The second stage synthesis reaction is the growth stage, the pH value in the reactor is adjusted to 10.5-11.5, the reaction temperature is 40-70°C, the stirring speed of the stirring paddle 2 is 500-1000rpm, and the total reaction is 40-120h. During the reaction, the solid content in the reactor is continuously increased to 200-1000g / L through the concentration equipment. When the target particle size is grown, the liquid is stopped. After aging, alkali washing and water washing, the filter cake is obtained by alternating washing and filtering. The filter cake is dried at 100-150°C for 3-24h to obtain a positive electrode material precursor for sodium ion batteries.

[0094] The third aspect of the present invention provides a positive electrode material precursor prepared by the above preparation method.

[0095] A fourth aspect of the present invention provides a positive electrode material for a sodium ion battery, characterized in that the positive electrode material for a sodium ion battery is prepared from the above-mentioned positive electrode material precursor.

[0096] In the present invention, when the above-mentioned cathode material precursor is used to prepare a cathode material for a sodium ion battery, the high sphericity, narrow particle size distribution and uniform metal element distribution of the cathode material precursor for a sodium ion battery can be directly transferred to the cathode material, so that the Cu element in the cathode material can be evenly distributed, overcoming the defect that the Cu element is easy to segregate, so that the sodium ion battery containing the cathode material has excellent capacity performance and cycle performance.

[0097] According to the present invention, the positive electrode material for sodium ion battery has a composition shown in formula II:

[0098] Na b (Mn x Fe y Ni z Cu w M a ) c O2 Formula II;

[0099] Among them, b=0.9-1.1, b+c=2, 0.3≤x≤0.5, 0.2≤y≤0.4, 0.1≤z≤0.3, 0.05≤w≤0.15, a=1-xyzw; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.

[0100] Further, 0.35<x<0.45, 0.25<y<0.35, 0.15<z<0.25, 0.08<w<0.12, a=1-xyzw.

[0101] Furthermore, M is selected from at least one of Al, Ti, Nb, V, Mg, B and Y, and furthermore, M is Mg.

[0102] According to the present invention, the actual content of Cu element at any position in the positive electrode material is w" and the theoretical content of Cu element in the positive electrode material satisfies the following relationship:

[0103] Δw c =︱w”-w︱ / w<8%.

[0104] The metal elements in the positive electrode material are evenly distributed, and in particular, the actual content of the Cu element at any position is slightly different from the theoretical content, indicating that the Cu element in the positive electrode material is evenly distributed without segregation. When the positive electrode material is used in a sodium ion battery, the capacity performance and cycle performance of the sodium ion battery can be significantly improved.

[0105] In the present invention, the actual content of Cu element at any position in the positive electrode material is w" and is measured by EDS method.

[0106] In the present invention, when the actual content w" of the Cu element is tested, the area of ​​the selected position accounts for 1-30% of the area of ​​the selected positive electrode material precursor particles. In the present invention, when ensuring that the area of ​​the selected position when testing the actual content w" of the Cu element meets the above range, it can not only ensure the feasibility of the test, but also effectively avoid the averaging effect, thereby better characterizing the uniformity of the distribution of the Cu element.

[0107] Furthermore, Δw c =︱w”-w︱ / w<3%.

[0108] According to the present invention, the compaction density of the positive electrode material is ≥2.8g / cm 3 .

[0109] In the present invention, the positive electrode material has a high compaction density, so that the sodium ion battery containing the positive electrode material has a high charge and discharge capacity.

[0110] Furthermore, the compaction density of the positive electrode material is ≥3g / cm 3 , preferably ≥3.2g / cm 3 .

[0111] A fifth aspect of the present invention provides a method for preparing the above-mentioned positive electrode material for a sodium ion battery, characterized in that the method comprises the following steps:

[0112] The positive electrode material precursor is mixed with a sodium source and then sintered to obtain the positive electrode material.

[0113] According to the present invention, the sodium source is selected from at least one of sodium hydroxide, sodium carbonate and sodium nitrate.

[0114] According to the present invention, the amounts of the cathode material precursor and the sodium source are such that: 0.9≤n(Na) / n[n(Mn)+n(Fe)+n(Ni)+n(Cu)+n(M)]≤1.1.

[0115] Furthermore, the amounts of the positive electrode material precursor and the sodium source are such that: 0.95≤n(Na) / n[n(Mn)+n(Fe)+n(Ni)+n(Cu)+n(M)]≤1.05.

[0116] According to the present invention, the sintering conditions include: a sintering temperature of 700-1000° C.; and a sintering time of 4-20 hours.

[0117] Furthermore, the sintering conditions include: a sintering temperature of 850-950° C.; and a sintering time of 6-15 hours.

[0118] A sixth aspect of the present invention provides a sodium ion battery, characterized in that the sodium ion battery comprises the above-mentioned positive electrode material for sodium ion battery.

[0119] The present invention will be described in detail below through examples.

[0120] In the following examples and comparative examples, the raw materials used are all commercially available products.

[0121] In the following examples and comparative examples, the properties involved are obtained by the following methods:

[0122] Particle size test: Malvern laser particle size analyzer Mastersizer 2000 was used for testing.

[0123] Morphology test: obtained by scanning electron microscope S-4800 of Hitachi, Japan;

[0124] The actual content of Cu element at any position in the positive electrode material precursor is w' and the actual content of Cu element at any position in the positive electrode material is w", through the 50mm 2 The EDS test of the model is obtained;

[0125] Specific surface area: obtained by testing with the Tristar II3020 specific surface area tester of Micromertics, USA;

[0126] Tap density: obtained by testing with the BT-30 tap density tester of Baxter;

[0127] Compacted density: obtained by testing with the MCP-PD51 compacted density meter produced by Mitsubishi Chemical of Japan;

[0128] Electrochemical performance test: The electrochemical performance of the 2025 button cell was tested at 25°C using the Xinwei battery test system. The prepared button cell was charged and discharged at 2.0-4.0V and 0.1C to evaluate the initial charge and discharge capacity of the material; the prepared button cell was cycled 80 times at 2.0-4.0V and 1C to evaluate the cycling performance of the material.

[0129] The assembly method of 2025 button battery is as follows:

[0130] First, the positive electrode material for sodium ion batteries, acetylene black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, coated on aluminum foil and dried, and stamped into a positive electrode sheet with a diameter of 11mm and a thickness of 60μm at a pressure of 100MPa. The positive electrode sheet was then placed in a vacuum drying oven and dried at 120℃ for 12h. The negative electrode used a sodium metal sheet with a diameter of 15.6mm and a thickness of 0.45mm; the diaphragm used a polyethylene porous membrane with a thickness of 25μm; the electrolyte used an equal mixture of 1mol / L NaPF6, ethylene carbonate (EC) and diethyl carbonate (DEC).

[0131] The positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into a 2025 button cell in an Ar gas glove box with a water content and an oxygen content of less than 5 ppm, and the cell at this time was regarded as an unactivated cell.

[0132] After making the button cell, place it for 6 hours. After the open circuit voltage stabilizes, use a current of 0.1C to charge to a cut-off voltage of 4.0V, and charge at a constant voltage of 4.0V to a cut-off current of 0.01C. Then discharge to a cut-off voltage of 2.0V at the same current density, and repeat the above method once more. The battery at this time is regarded as an activated battery.

[0133] Example 1

[0134] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0135] The preparation method of the positive electrode material precursor is as follows, and during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula.

[0136] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0137] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0138] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P1.

[0139] The sphericity of the positive electrode material precursor is Q = 99%, and the particle size distribution is K 90 is 0.60, the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.92g / cm 3 , tap density TD is 1.25g / cm 3 , BET is 28m 2 / g. The details are shown in Table 1.

[0140] Figure 2 This is a SEM image of the cathode material precursor P1 provided in Example 1 at 30K times. It can be seen from the image that the cathode material precursor P1 is a secondary sphere formed by agglomeration of primary particles, and has good sphericity. Figure 3 This is a 2K-fold SEM image of the cathode material precursor P1 provided in Example 1. It can be seen from the image that the particles of the cathode material precursor P1 are relatively uniform in size without fine powder, that is, it has a narrow particle size distribution. Figure 6 The distribution diagram of Mn, Ni, Fe and Cu elements obtained by performing EDS energy spectrum scanning on the positive electrode material precursor P1 of Example 1 shows that the four elements are evenly distributed without element segregation.

[0141] Randomly select any two positions of the cathode material precursor P1, such as Figure 7As shown, the area of ​​position 1 is 2% of the area of ​​secondary particles in the positive electrode material precursor P1. The area of ​​position 2 is 2% of the area of ​​secondary particles in the positive electrode material precursor P1. EDS was used to test the Cu element content at position 1 and position 2, and the measured values ​​are shown in Table 2.

[0142] Example 2

[0143] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0144] The preparation method of the positive electrode material precursor is as follows, and during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula.

[0145] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0146] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.5.

[0147] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120°C for 6 hours to obtain the positive electrode material precursor P2.

[0148] The sphericity Q of the positive electrode material precursor P2 is 93%, and the particle size distribution K 90 is 0.75, the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.53g / cm 3 , the tap density TD is 0.68g / cm 3 , BET is 68m 2 / g.

[0149] Example 3

[0150] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0151] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0152] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0153] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.8.

[0154] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P3.

[0155] The positive electrode material precursor P3 has a sphericity Q=92% and a particle size distribution K 90 is 0.81, and the median particle size D 50 The diameter is 3.5 μm and the bulk density AD is 0.56 g / cm 3 , tap density TD is 0.72g / cm 3 , BET is 54m 2 / g.

[0156] Example 4

[0157] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0158] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0159] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=20.

[0160] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0161] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage, the pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing and filtration, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P4 for sodium ion batteries.

[0162] The sphericity Q of the positive electrode material precursor P4 is 93%, and the particle size distribution K 90 is 0.63, the median particle size D 50 The diameter is 3.5 μm and the bulk density AD is 0.82 g / cm 3 , the tap density TD is 0.94g / cm 3 , BET is 37m 2 / g.

[0163] Example 5

[0164] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0165] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0166] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=1.2.

[0167] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0168] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P5.

[0169] The positive electrode material precursor P5 has a sphericity Q=95% and a particle size distribution K 90 is 0.72, and the median particle size D 50 The diameter is 3.5 μm and the bulk density AD is 0.78 g / cm 3 , the tap density TD is 0.91g / cm 3 , BET is 33m 2 / g.

[0170] Example 6

[0171] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0172] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0173] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=20.

[0174] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.8.

[0175] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P6.

[0176] The sphericity Q of the positive electrode material precursor P6 is 91%, and the particle size distribution K 90 is 0.84, the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.45g / cm 3 , tap density TD is 0.85g / cm 3 , BET is 69m 2 / g.

[0177] Example 7

[0178] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.3 Fe 0.4 Ni 0.2 Cu 0.1 (OH)2.

[0179] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0180] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0181] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0182] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P7.

[0183] The positive electrode material precursor P7 has a sphericity Q=98% and a particle size distribution K 90 is 0.66, and the median particle size D 50 The diameter is 5.5μm and the bulk density AD is 0.84g / cm 3 , tap density TD is 1.03g / cm 3 , BET is 36m 2 / g.

[0184] Example 8

[0185] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.5 Fe 0.2 Ni 0.15 Cu 0.15 (OH)2.

[0186] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0187] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0188] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0189] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P8.

[0190] The sphericity Q of the positive electrode material precursor P8 is 94%, and the particle size distribution K 90 is 0.79, the median particle size D 50 8μm, bulk density AD is 0.96g / cm 3 , the tap density TD is 1.42g / cm 3 , BET is 25m 2 / g.

[0191] Example 9

[0192] This embodiment provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.09 Mg 0.01 (OH)2.

[0193] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0194] Manganese sulfate, ferrous sulfate, nickel sulfate and magnesium sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=5.

[0195] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 0.25.

[0196] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage. The pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor P9.

[0197] The positive electrode material precursor P9 has a sphericity Q=98% and a particle size distribution K 90 is 0.62, and the median particle size D 50 The diameter is 3.5 μm and the bulk density AD is 0.91 g / cm 3 , tap density TD is 1.17g / cm 3 , BET is 32m 2 / g.

[0198] Example 10

[0199] The Mg element in Example 8 was replaced by Nb element, and other process conditions remained unchanged. The obtained positive electrode material precursor P10 had a composition of Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.09 Nb 0.01 (OH)2. The sphericity Q of the positive electrode material precursor P10 is 97%, and the particle size distribution K 90 is 0.65, the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.89g / cm 3 , tap density TD is 1.15g / cm 3 , BET is 38m 2 / g.

[0200] Embodiment 11

[0201] The Mg element in Example 8 was replaced by the Ti element, and the other process conditions remained unchanged. The positive electrode material precursor P11 was obtained, and its composition was Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.09 Ti 0.01 (OH)2. The sphericity of the positive electrode material precursor P11 is Q = 97%, and the particle size distribution is K 90 is 0.66, and the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.92g / cm 3 , tap density TD is 1.27g / cm 3 , BET is 34m 2 / g.

[0202] Comparative Example 1

[0203] This comparative example provides a positive electrode material precursor, the chemical formula of which is Mn 0.4 Fe 0.3 Ni 0.2 Cu 0.1 (OH)2.

[0204] The preparation method of the positive electrode material precursor is as follows, during the preparation process, the molar ratio of manganese, nickel, iron and copper in the liquid is ensured to be consistent with the chemical formula:

[0205] Manganese sulfate, ferrous sulfate and nickel sulfate are dissolved in pure water to obtain a first metal salt solution; copper sulfate is dissolved in pure water to obtain a second metal salt solution. The first metal salt solution is fed into the reactor through a first liquid inlet pipe, and the second metal salt solution is fed into the reactor through a second liquid inlet pipe. The distance between the first liquid inlet pipe and the bottom of the reactor is L1, the distance between the second liquid inlet pipe and the bottom of the reactor is L2, and the ratio of L2 to L1 is γ=L2 / L1=0.5.

[0206] Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the sodium hydroxide aqueous solution and aqueous ammonia are contacted to carry out a synthesis reaction; by adjusting the inlet flow rate of the aqueous ammonia, the ratio β of the amount of substance of the aqueous ammonia to the amount of substance of the copper ions is made to be 1.3.

[0207] The reaction process is divided into two stages. Among them, the pH value of the granulation stage is 12.2, the rotation speed is 800rpm, and the total reaction time is 20h. After that, it is the growth stage, the pH value in the reactor is adjusted to 11.1, the rotation speed is 800rpm, and the solid content in the reactor is continuously increased to 600g / L through the concentration equipment during the reaction. When the target particle size is grown, the liquid is stopped. After aging, washing, and filtering, the filter cake is obtained. The filter cake is dried at 120 degrees for 6 hours to obtain the positive electrode material precursor DP1.

[0208] The sphericity Q of the positive electrode material precursor DP1 is 72%, and the particle size distribution K 90 is 1.55, the median particle size D 50 The diameter is 3.5μm and the bulk density AD is 0.34g / cm 3 , the tap density TD is 0.42g / cm 3 , BET is 112m 2 / g.

[0209] Figure 4 This is a SEM image of the positive electrode material precursor DP1 provided in Comparative Example 1 at 30K times. It can be seen from the image that the sphericity of the positive electrode material precursor is poor; Figure 5 This is a SEM image of the positive electrode material precursor DP2 provided in Comparative Example 1 at 2K times. It can be seen from the image that the particles of the material are of different sizes, including fine powder, that is, the particle size distribution is very wide. Figure 8 The distribution diagram of Mn, Ni, Fe and Cu elements obtained by EDS spectrum scanning of the positive electrode material precursor DP1 of comparative example 1 shows that the elements are not evenly distributed at the atomic level and the copper element is severely segregated.

[0210] In addition, any two positions of the positive electrode material precursor DP1 are randomly selected, such as Fig. 9 As shown, the area of ​​position 1 is 2% of the area of ​​secondary particles in the positive electrode material precursor DP1. The area of ​​position 2 is 2% of the area of ​​secondary particles in the positive electrode material precursor DP1. EDS was used to test the Cu element content at position 1 and position 2, and the measured values ​​are shown in Table 2.

[0211] Table 1

[0212]

[0213] Table 2

[0214]

[0215]

[0216] It can be seen from Table 1 and Table 2 that, compared with Comparative Example 1, the cathode material precursors provided by Examples 1-11 of the present invention have high sphericity, narrow particle size distribution, and the metal elements, especially the Cu element, are evenly distributed.

[0217] Application Example 1

[0218] The positive electrode material precursor P1 of Example 1 was mixed with sodium carbonate in a molar ratio of n(Na) / n[n(Mn)+n(Fe)+n(Ni)+n(Cu)+n(M)]=1, sintered at 850°C, kept warm for 8h, cooled and sieved to obtain the positive electrode material A1 for sodium ion battery.

[0219] The composition of the positive electrode material A1 for sodium ion battery is shown in Table 3. The compaction density of the positive electrode material is tested, and the results are shown in Table 3. Randomly select any two positions of the positive electrode material, such as Fig.10 As shown, the area of ​​position 1 is 2% of the area of ​​the secondary particles in the positive electrode material A1. The area of ​​position 2 is 2% of the area of ​​the secondary particles in the positive electrode material A1. EDS was used to test the Cu element content at position 1 and position 2, and the measured values ​​are shown in Table 4.

[0220] Application Example 2-11

[0221] The positive electrode material for sodium ion battery was prepared according to the method of Application Example 1, except that the positive electrode material precursors P2-P11 were mixed with sodium carbonate respectively to obtain positive electrode materials A2-A11 for sodium ion battery.

[0222] Comparative application example 1

[0223] The positive electrode material for sodium ion battery was prepared according to the method of Application Example 1, except that the positive electrode material precursor DP1 was mixed with sodium carbonate to obtain the positive electrode material D1 for sodium ion battery.

[0224] Randomly select any two positions of the positive electrode material, such as Fig.11 As shown, the area of ​​position 1 is 2% of the area of ​​the secondary particles in the positive electrode material D1. The area of ​​position 2 is 2% of the area of ​​the secondary particles in the positive electrode material D1. EDS was used to test the Cu element content at position 1 and position 2, and the measured values ​​are shown in Table 4.

[0225] Table 3

[0226] Cathode Materials composition <![CDATA[Compaction density / g / cm 3 > Application Example 1 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.3 Application Example 2 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.12 Application Example 3 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.04 Application Example 4 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.14 Application Example 5 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.19 Application Example 6 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 3.05 Application Example 7 <![CDATA[Na(Mn 0.3 Feb 0.4 Ni 0.2 Cu 0.1 )O2]]> 3.15 Application Example 8 <![CDATA[Na(Mn 0.5 Feb 0.2 Ni 0.15 Cu 0.15 )O2]]> 3.18 Application Example 9 <![CDATA[Na(Mn 0.4 Fe 0.3 Aunt 0.2 The 0.09 Mg 0.01 )O2]]> 3.26 Application Example 10 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.09 No 0.01 )O2]]> 3.21 Application Example 11 <![CDATA[Na(Mn 0.4 Fe 0.3 us 0.2 With 0.09 IT 0.01 )O2]]> 3.25 Comparative application example 1 <![CDATA[Na(Mn 0.4 Feb 0.3 Ni 0.2 Cu 0.1 )O2]]> 2.5

[0227] Table 4

[0228] serial number Theoretical value w Position 1 measured value w1" <![CDATA[Δw c1 ]]> Measured value at position 2 w2" <![CDATA[Δw c2 ]]> Application Example 1 0.1 0.09832 1.68% 0.10232 2.32% Application Example 2 0.1 0.09736 2.64% 0.10289 2.89% Application Example 3 0.1 0.09692 3.08% 0.10302 3.02% Application Example 4 0.1 0.09745 2.55% 0.10245 2.45% Application Example 5 0.1 0.09687 3.13% 0.10315 3.15% Application Example 6 0.1 0.09745 2.55% 0.10297 2.97% Application Example 7 0.1 0.09758 2.42% 0.10277 2.77% Application Example 8 0.15 0.14657 2.29% 0.15375 2.50% Application Example 9 0.09 0.08784 2.40% 0.09302 3.36% Application Example 10 0.09 0.08777 2.48% 0.09262 2.91% Application Example 11 0.09 0.08704 3.29% 0.09232 2.58% Comparative application example 1 0.1 0.07562 24.38% 0.29457 194.57%

[0229] It can be seen from Tables 3 and 4 that, compared with Comparative Application Example 1, the positive electrode materials provided by Application Examples 1-11 of the present invention have a high compaction density. In particular, the metal elements, especially the Cu element, in the positive electrode materials provided by the present invention are evenly distributed.

[0230] Test Case

[0231] The positive electrode materials of the application example and the comparative application example were composed into a sodium ion battery, and the electrochemical performance of the sodium ion battery was tested. The results are shown in Table 5.

[0232] Table 5

[0233]

[0234]

[0235] It can be seen from the results in Table 5 that, compared with Comparative Example 1, the 0.1C discharge capacity and the capacity retention rate of 80 cycles at 1C of the sodium ion battery containing the positive electrode material provided by the present invention are significantly improved.

[0236] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cathode material precursor, characterized in that: The positive electrode material precursor is spherical and / or quasi-spherical; the sphericity Q of the positive electrode material precursor satisfies: 90%<Q<100%; The cathode material precursor D 10 , D 50 and D 90 Satisfy: 0.55<K 90 =(D 90 -D 10 ) / D 50 <0.79; Where, Q = 4π × S / (L 2 )×100%, S is the projected area of ​​the precursor secondary particle, and L is the projected perimeter of the precursor secondary particle; The actual content of Cu element at any position in the positive electrode material precursor is w' and the theoretical content of Cu element in the positive electrode material precursor is w, which satisfies the following relationship: Δw p =︱w'-w︱ / w<10%; The cathode material precursor has a composition shown in Formula I: Mn x Fe y Ni z Cu w M a (OH)2 of formula I; Among them, 0.3≤x≤0.5, 0.2≤y≤0.4, 0.1≤z≤0.3, 0.05≤w≤0.15, a=1-xyzw; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.

2. The cathode material precursor according to claim 1, wherein 93%<Q<100%; and / or, 0.57<K 90 =(D 90 -D 10 ) / D 50 <0.

75.

3. The cathode material precursor according to claim 1 or 2, wherein: The positive electrode material precursor is secondary particles formed by agglomeration of primary particles.

4. The cathode material precursor according to claim 1 or 2, wherein: 0.35<x<0.45, 0.25<y<0.35, 0.15<z<0.25, 0.08<w<0.12, a=1-xyzw; And / or, M is selected from at least one of Al, Ti, Nb, V, Mg, B and Y.

5. The cathode material precursor according to claim 4, wherein: M is Mg.

6. The cathode material precursor according to claim 1 or 2, wherein: The actual content of Cu element at any position in the positive electrode material precursor is w' and the theoretical content of Cu element in the positive electrode material precursor is w, which satisfies the following relationship: Δw p =︱w'-w︱ / w<5%。 7. The cathode material precursor according to claim 1 or 2, wherein: The median particle size D of the positive electrode material precursor 50 3-10μm.

8. The cathode material precursor according to claim 7, wherein: The median particle size D of the positive electrode material precursor 50 3.5-8μm.

9. The cathode material precursor according to claim 8, wherein: The median particle size D of the positive electrode material precursor 50 3.5-5.5μm.

10. The cathode material precursor according to claim 1 or 2, wherein: The bulk density AD of the positive electrode material precursor is 0.3-1.0 g / cm 3 .

11. The cathode material precursor according to claim 1 or 2, wherein: The bulk density AD of the positive electrode material precursor is 0.45-0.75 g / cm 3 .

12. The cathode material precursor according to claim 1 or 2, wherein: The tap density TD of the positive electrode material precursor is 0.6-1.5 g / cm 3 .

13. The cathode material precursor according to claim 12, wherein: The tap density TD of the positive electrode material precursor is 0.7-1.3 g / cm 3 .

14. The cathode material precursor according to claim 1 or 2, wherein: The specific surface area of ​​the positive electrode material precursor is 20-70 m 2 / g.

15. The cathode material precursor according to claim 14, wherein: The specific surface area of ​​the positive electrode material precursor is 30-45m 2 / g.

16. A method for preparing a cathode material precursor according to any one of claims 1 to 15, characterized in that: The preparation method comprises the following steps: (1) mixing a soluble manganese salt, a ferrous salt, a nickel salt and an optional M salt with water to obtain a first metal salt solution; mixing a soluble copper salt with water to obtain a second metal salt solution; mixing a precipitant with water to obtain a precipitant solution; (2) The first metal salt solution is introduced into the reactor through a first liquid inlet pipe, and the second metal salt solution is introduced into the reactor through a second liquid inlet pipe; the distance L1 between the first liquid inlet pipe and the bottom of the reactor and the distance L2 between the second liquid inlet pipe and the bottom of the reactor satisfy: γ=L2 / L1>1; (3) Under the protection of an inert atmosphere, the first metal salt solution, the second metal salt solution, the precipitant solution and ammonia water are simultaneously introduced into a reaction kettle to perform a synthesis reaction to obtain a slurry, which is then aged, washed and filtered to obtain a filter cake, which is then dried to obtain the positive electrode material precursor, wherein the ratio β of the amount of ammonia water to the amount of copper ions is controlled to satisfy: 0<β<0.

8.

17. The preparation method according to claim 16, wherein: 2≤γ≤8; And / or, 0.15≤β≤0.

6.

18. The preparation method according to claim 17, wherein: 0.15≤β≤0.4。 19. The preparation method according to any one of claims 16 to 18, wherein: The conditions of the synthesis reaction include: reaction temperature of 40-70° C. and stirring speed of 500-1000 rpm.

20. The preparation method according to any one of claims 16 to 18, wherein: The synthetic reaction comprises the following steps: S1, controlling the pH of the reactor to 11.5-12.5, and carrying out the first stage synthesis reaction; S2. Control the pH of the reactor to 10.5-11.5 and carry out the second stage synthesis reaction.

21. The preparation method according to claim 20, wherein: The reaction temperature of the first stage synthesis reaction is 40-70°C, the reaction time is 5-30h, and the stirring speed is 500-1000rpm; And / or, the synthesis reaction makes the solid content of the slurry in the reactor be 200-1000 g / L.

22. The preparation method according to any one of claims 16 to 18, wherein: The washing conditions include: washing by alternating alkali washing and water washing until the filtrate is neutral; And / or, the drying conditions are: drying temperature is 100-150° C., and drying time is 3-24 hours.

23. A positive electrode material for a sodium ion battery, characterized in that: The positive electrode material for sodium ion battery is prepared from the positive electrode material precursor according to any one of claims 1 to 15.

24. The positive electrode material for sodium ion battery according to claim 23, wherein The positive electrode material for sodium ion battery has a composition shown in Formula II: Na b (Mn x Fe y Ni z Cu w M a ) c Oxygen formula II; Among them, b=0.9-1.1, b+c=2, 0.3≤x≤0.5, 0.2≤y≤0.4, 0.1≤z≤0.3, 0.05≤w≤0.15, a=1-xyzw; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.

25. The positive electrode material for sodium ion battery according to claim 24, wherein 0.35<x<0.45, 0.25<y<0.35, 0.15<z<0.25, 0.08<w<0.12, a=1-xyzw; And / or, M is selected from at least one of Al, Ti, Nb, V, Mg, B and Y.

26. The positive electrode material for sodium ion battery according to claim 25, wherein M is Mg.

27. The positive electrode material for sodium ion battery according to any one of claims 23 to 26, wherein: The actual content of Cu element at any position in the positive electrode material is w'' and the theoretical content of Cu element in the positive electrode material is w, which satisfies the following relationship: Δw c =︱w''-w︱ / w<8%。 28. The positive electrode material for sodium ion battery according to claim 27, wherein The actual content of Cu element at any position in the positive electrode material is w'' and the theoretical content of Cu element in the positive electrode material is w, which satisfies the following relationship: Δw c =︱w''-w︱ / w<3%。 29. The positive electrode material for sodium ion battery according to any one of claims 23 to 26, wherein: The compaction density of the positive electrode material is ≥2.8 g / cm 3 .

30. The positive electrode material for sodium ion battery according to claim 29, wherein The compaction density of the positive electrode material is ≥3 g / cm 3 .

31. The positive electrode material for sodium ion battery according to claim 30, wherein The compaction density of the positive electrode material is ≥3.2 g / cm 3 .

32. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 23 to 31, characterized in that: The method comprises the following steps: The positive electrode material precursor according to any one of claims 1 to 15 is mixed with a sodium source and then sintered to obtain the positive electrode material.

33. The method for preparing a positive electrode material for a sodium ion battery according to claim 32, wherein: The sodium source is selected from at least one of sodium hydroxide, sodium carbonate and sodium nitrate; And / or, the amounts of the positive electrode material precursor and the sodium source are such that: 0.9≤n(Na) / n[n(Mn)+n(Fe)+n(Ni)+n(Cu)+n(M)]≤1.1; And / or, the sintering conditions include: a sintering temperature of 700-1000° C. and a sintering time of 4-20 hours.

34. The method for preparing a positive electrode material for a sodium ion battery according to claim 33, wherein: The sintering conditions include: a sintering temperature of 850-950° C. and a sintering time of 6-15 hours.

35. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode material for a sodium ion battery according to any one of claims 23 to 31.

Citation Information

Patent Citations

  • A Cu-Fe-Mn layere oxide precursor for sodium ion battery and preparation method and application thereof

    CN108963233A

  • Ternary precursor doped with metal elements as well as preparation method and application of ternary precursor

    CN113582249A

  • Nickel-iron-manganese ternary precursor for sodium ion battery as well as preparation method and application of nickel-iron-manganese ternary precursor

    CN115196691A